A Single-Chip 10-Band WCDMA/HSDPA 4-Band GSM/EDGE SAW-less CMOS Receiver With DigRF 3G Interface and 90 dBm IIP2 - Kaczman, D.; Shah, M.; Alam, M.; Rachedine, M.; Cashen, D.; Lu Han; Raghavan, A. (IEEE journal of solid-state circuits, 2009)
This paper describes the design and performance of a 90 nm CMOS SAW-less receiver with DigRF interface that supports 10 WCDMA bands (I, II, III, IV, V, VI, VIII, IX, X, XI) and 4 GSM bands (GSM850, EGSM900, DCS1800, PCS1900). The receiver is part of a single-chip SAW-less transceiver reference platform IC for mass-market smartphones, which has been designed to meet Category 10 HSDPA (High Speed Downlink Packet Access) requirements. The novel receiver core consists of a single-stage transconductance amplifier (TCA) with large gain control range, a current commutating passive mixer enhanced for automatic on chip IIP2 calibration with 25% duty-cycle LO injection and threshold adjust, and current-input complex Direct Coupled Filter (DCF). The low noise TCAs are designed without inductive loads to save area. A self-contained on chip automatic IIP2 calibration system with algorithm routine, implemented in firmware, is used to optimize IIP2 performance. This topology eliminates the external LNA, inter-stage SAW filter and transimpedance amplifier (TZA) in conventional WCDMA designs and results in current drain and die area savings as well as improved noise. The 25% duty-cycle LO injection, with threshold adjustment, into a current driven passive double-balanced mixer results in 3 dB additional gain, lower noise figure and lower intermodulation distortion. Large signal blocking and 1/f noise performance are improved significantly by eliminating the 0 and 180deg LO signal crossover at the mixer. The full receiver achieves 2.2 dB/2.39 dB simplex/duplex NF (with - 24.5 dBm TX leakage), > 90 dBm complex two-tone IIP2, 60 dB gain and - 1/+ 5 dBm half/full-duplex image IIP3. The receiver core consumes only 15.1 mA from a 1.5 V supply.